觀測與模擬研究電離層與大氣波動耦合 - 周敏揚; Chou, Min-Yang (2018)
劇烈的氣象天氣系統常伴隨著旺盛發展的對流，不穩定的對流系統可以在低層大氣產生波動並向上傳至高層大氣，影響地球的太空環境。大氣波動在低層與高層大氣之間的垂直耦合扮演著重要的角色，他們可以改變高層大氣結構引發電離層變異性與不穩定現象，進一步影響全球定位、導航、偵察系統與無線電波通訊。除了天氣系統之外，隨著科技的進步與發展，自1960年代以來已經有許多研究指出人類發射火箭太空船引發的大氣波動亦對電離層造成嚴重的影響，了解自然災害與人為因素如何影響高層大氣變成一個非常重要的議題。因此本論文利用全球導航衛星系統(Global Navigation Satellite System, GNSS)與美國海軍研究實驗室(Naval Research Laboratory, NRL) SAMI3/ESF電離層模式研究自然災害與人類太空活動兩種不同的來源對電離層的影響。 在自然災害方面，我們研究2016年七月與九月襲擊台灣的超級強颱尼伯特與莫蘭蒂造成的電離層擾動現象。莫蘭蒂颱風是2016年最強颱風，我們利用GNSS全電子含量觀測到莫蘭蒂颱風引發之同心圓移行電離層擾動。此同心圓擾動展現不同的時間與空間特徵尺度符合重力波理論，證實此擾動為颱風產生之同心圓重力波，這也是史上首次在太空中觀測到颱風產生的同心圓擾動。而尼伯特颱風事件，也首次在低緯度地區觀測到夜間中尺度移行電離層擾動現象。夜間中尺度電離層擾動主要發生在中緯度地區，我們推論此夜間中尺度移行電離層擾動為颱風引發之同心圓重力波與電離層Perkins不穩定機制耦合產生之電離層不穩定現象。同時也利用SAMI3/ESF模式去模擬與驗證同心圓重力波與夜間中尺度移行電離層擾動現象之間的耦合關係。本研究證實了颱風產生的同心圓重力波除了可以向上傳至電離層造成電離層擾動外，也會影響電離層電動力學，進一步造成赤道地區夜間電離層不穩定現象。 在人類太空活動方面，我們針對SpaceX獵鷹九號JASON-3任務、福衛五號 (FORMOSAT-5)任務與獵鷹重型火箭任務這三個案例去探討火箭發射對太空環境造成的影響。利用GNSS全電子含量觀測到火箭在低熱氣層與電離層中產生大氣重力波與聲震波。研究發現火箭產生的電離層擾動相對於天氣對流系統引發的電離層擾動特徵頻譜比較單調ㄧ致。JASON-3任務中，我們首次在電離層中觀測到火箭產生的V形聲震波與同心圓移行電離層擾動。此同心圓移行電離層擾動特徵符合重力波理論，推測此擾動為火箭引發的同心圓重力波。利用波源分析法與重力波射線追蹤法推測此同心圓重力波可能為第二節火箭在中氣層頂區域產生並向上傳至電離層。在福衛五號任務中，火箭在加州上方產生了巨大的圓形聲震波與電離層洞。由於火箭近垂直發射運送衛星至720公里高的任務軌道，在飛行過程中產生了圓型衝擊波，也間接證實了電離層擾動波形與火箭姿態幾何有相當大關係。在獵鷹重型火箭任務中，我們觀測到火箭產生的電離層擾動往北傳達上千公里，此電離層擾動展現短周期特徵尺度與ㄧ致的傳播速度。利用重力波理論推測此海潮波形的電離層擾動可能是低熱氣層中水平傳播的導管重力波(Ducted gravity wave)。由於短周期重力波難以向上傳至電離層，利用SAMI3/ESF模式模擬結果顯示，電動力學耦合(electrodynamic coupling)效應可能為導管重力波引發短周期電離層擾動的主要機制。隨著科技的持續進展，未來將會有越來越多火箭發射任務，本研究有助於深入了解人類活動如何影響大氣與太空環境。 The Earth’s ionosphere is strongly influenced by meteorological processes originating from the lower atmosphere they can affect the ionosphere through the upward propagating atmospheric waves Atmospheric waves play a crucial role in coupling the lower and upper atmosphere they can modify and modulate the ionospheric electrodynamics driving ionospheric variability and instabilities to make considerable impacts on the performances of positioning navigation reconnaissance systems and radio communication applications Since the 1960s several studies have reported that rocket launches also contribute to the ionospheric variability In this dissertation we study the ionospheric responses to natural and anthropogenic sources using the ground-based Global Navigation Satellite Systems networks (GNSS) and Naval Research Laboratory (NRL) SAMI3/ESF (Sami 3 is Also a Model of the Ionosphere) model For natural sources two Category 5 Super Typhoon Meranti and Nepartak triggered traveling ionospheric disturbances (TIDs) are studied when they swept toward Taiwan in 2016 Super Typhoon Meranti excited evident concentric waves in GNSS total electron content (TEC) are first observed These concentric waves with various scales agree well with the internal Boussinesq dispersion relation suggesting that they are associated with the primary gravity waves instead of secondary waves Additionally Perkins-type ionospheric instabilities related to Super Typhoon Nepartak are first investigated in the equatorial ionosphere Nighttime ionospheric instabilities are triggered following the concentric gravity waves it is suggested that the electrodynamic coupling between concentric gravity waves and Perkins instability may play an important role in seeding the instability SAMI3/ESF model is further used to confirm the interconnection between concentric gravity waves and ionospheric instabilities These studies provide new evidence that typhoon-induced concentric gravity waves can directly penetrate into the ionosphere modifying the ionospheric electrodynamics to trigger instabilities and disturbances in the equatorial ionosphere region For anthropogenic sources ionospheric responses to three SpaceX rocket launches comprising JASON-3 FORMOSAT-5 and Falcon Heavy missions are investigated GNSS TEC Observations show that these rocket launches can excite gravity waves and shock acoustic waves in the lower thermosphere and ionosphere causing ionospheric perturbations The rocket-induced TIDs display nearly a monochromatic spectrum that is very different from those waves generated by deep convection We report two remarkable patterns of V-shape shock acoustic waves and concentric TIDs (CTIDs) in the ionosphere during with the JASON-3 launch The characteristics of CTIDs agree well with the gravity wave dispersion relation suggesting that the CTIDs are related to the atmospheric gravity waves The optimal wave source searching and gravity wave raytracing technique suggests that the CTIDs were originated from the mesopause region after the ignition of the second-stage rocket The FORMOSAT-5 launch-induced gigantic circular shock waves and ionospheric plasma hole are studied This is the largest rocket-induced circular shock acoustic waves on record and is due to the unique nearly vertical attitude of the rocket during orbit insertion The Falcon Heavy launch-induced short-period and long-propagating TIDs are presented These short-period TIDs are most likely associated with ducted gravity waves trapping in a thermal duct Numerical simulations suggest that thermal ducted gravity waves can trigger TIDs through the electrodynamic coupling processes These studies provide a new insight into how the human activities affect our atmosphere and space environment as these anthropogenic space weather events are expected to increase at an enormous rate in the future 理學院 地球科學系 博碩士論文